Effectiveness of obesity prevention and control - Montarat Thavorncharoensap (Asian Development Bank Institute (ADBI), 2017)
Implementation of evidence-based interventions to control obesity is regarded as a public health priority. In this working paper, effectiveness and cost-effectiveness evidence of sugar-sweetened beverage (SSB) taxes, nutrition labeling, advertising bans on unhealthy food, and school-based interventions are reviewed. The review indicates that SSB taxes may be an effective and cost-effective intervention for obesity prevention and control. Regarding nutrition labeling, current evidence indicates that this has a significant impact on food selection. Although there is limited evidence on its impact on body mass index (BMI) and obesity prevalence, nutrition labeling is considered a cost-effective intervention in many settings. Further, while current evidence indicates that unhealthy food and beverage advertisements may increase dietary intake and the preference for unhealthy foods, especially in children, limited evidence demonstrates the impact of restricted unhealthy food advertising on BMI and obesity prevalence. However, such an intervention is considered to be cost-effective in many settings. Concerning school-based interventions, due to the limited number of good-quality studies as well as high variation across studies, the effectiveness of these interventions is inconclusive. Current evidence also suggests that school-based interventions are less likely to be cost-effective.
Keywords: I12; I18; 330; Economics; Health